Characteristics of Pain Based on Numerical Rating Scale in Maxillofacial Trauma Patients Treated with Open Reduction Internal Fixation - Yohanes Yoppy Purnomo; Endang Sjamsudin; Eka Marwansyah Oli'i (Nusantara Medical Science Journal, 2021)
Introduction: Open Reduction Internal Fixation (ORIF) is one of the maxillofacial bone fracture treatment procedures. Post-surgical pain is generally assessed by Numerical Rating Scale (NRS). Objective: To obtain information about pain characteristics in post-ORIF patients based on NRS. Methods: This study is an observational study with a retrospective descriptive approach. The research was conducted at Hasan Sadikin General Hospital (RSHS) Bandung in January 2018 - December 2019 based on medical record data. The data collected included age, gender, fracture area, diagnosis, duration of surgery, number of plates and screws, pre-surgical and post-surgical pain based on NRS, pain intensity measured every 8 hours postoperatively for 24 hours. Results: In this study, 65 medical records were obtained. The most frequent characteristics of the subjects were young adults aged 17-30 years (56.92%) and males (86.15%). The most frequent fracture locations were the mandible area (48.67%) and the most frequently performed surgery was at the mandibular area (60.46%). Regarding the duration of the surgery, most of the surgeries lasted for 61-120 minutes (32.30%) with the most used plates were plates (1-10 holes) and plates (11-20) holes, both having the same percentage (38.46%), and the most frequently used screw was screw (1-10) (49.23%). The most frequently used analgesics was Ketorolac (87.69%) and The NRS pain scale for ORIF was a mild type of surgery with an NRS scale of 1-3. The mean of pre-ORIF surgery patients showed a mild pain intensity with a percentage of 92.30% and postoperatively resulted in mild pain with a percentage of 95.38%. Conclusion: Characteristics of pain based on NRS in maxillofacial trauma patients treated with ORIF indicate mild pain and could be the result of the influence of analgesic drugs or subjective assessments, therefore, further research is needed to obtain a more precise assessment of the pain.